Paediatric hanging associated out of hospital cardiac arrest in Melbourne, Australia: characteristics and outcomes. Issue 5 (18th February 2011) - Deasy, C; Bray, J; Smith, K; Harriss, L R; Bernard, S A; Cameron, P
Abstract : Introduction: Hanging is a rare but devastating cause of out of hospital cardiac arrest (OHCA). The characteristics and outcomes of hanging associated OHCA in the paediatric age group are described. Methods: The Victorian Ambulance Cardiac Arrest Registry was searched for patients aged less than 18 years where the precipitant cause of OHCA was hanging. Results were cross checked with the coronial database. Results: During the years 2000–2009, there were 680 paediatric cardiac arrests of which 53 (7.8%) were precipitated by hanging with an incidence of 4.4 per million paediatric patients (<18 years) per year. Median age was 16 (IQR 14–17) years and 58.5% were males. Five were unintentional hangings; median age 3 (IQR 2–4) years. The youngest deliberate hanging associated OHCA was aged 10 years. Most hangings occurred in a house (85%) and bystander cardiopulmonary resuscitation (CPR) was performed in 30%. Asystole was the most common initial cardiac arrest rhythm seen in 50 cases (94%) while three patients had pulseless electrical activity. The emergency medical services (EMS) attempted resuscitation in 18 patients (34%), inserting an endotracheal tube in 13 patients. The majority (n=41) were not transported; seven patients were transported with return of spontaneous circulation (ROSC) and five patients were transported with ongoing CPR. Victims who had bystander CPR were more likely to have EMS attempted resuscitation (p<0.001). Only patients who had received bystander CPR achieved ROSC (p<0.001). Three patients survived to hospital discharge; two survivors suffered severe neurological injury (Cerebral Performance Category Scale 3–4). Conclusion: Non-intentional hanging is rare but deliberate hanging with suicidal intent represents a significant proportion of OHCAs in patients under 18 years of age. A focus on prevention is key, as outcomes are poor, with survivors likely to suffer a severe neurological insult.